Efektivitas Ekstrak Kulit Manggis (Garcinia Mangostana Linn) Terhadap Status Kesehatan Gingiva Penyandang Tunanetra Di Unit Rehabilitasi Sosial Bhakti Candrasa Surakarta - Pratiwi, Firdayanti Indah (2016)
Plaque and bacterial is either triggers of dental and oral diseases, suppose that gingivitis especially on blind. Therefore it is necessary to do various treatment, such chemical method with a solution containing the anti inflammatory and antibacterial agent. Mangosteen fruit peel extract is an ingredient that contains chemical compounds that have an important role in inhibiting the formation of dental plaque. Nowadays mangosteen fruit peel extract is process in the packaging like Mastin®. The purpose of this study was to determine the effectivity of mangosteen fruit peels extract (garcinia mangostana linn) on gingival health status of blind in Bhakti Candrasa Sosial Rehabilitation Unit. Method that used was observational analytic with pretest and posttest design approach. The respondents were blind aged 35-49 years in Bhakti Candrasa Sosial Rehabilitation Unit. This study was conducted in may 2016. This study uses purposive sampling method. Respondents were treated to gargle twice a day, at the morning and afternoon and assessment using the modified gingival index (MGI). Examinationconducted at the first molars right upper (16), first incisivus left upper (21), first premolar left upper (24), first molar left lower (36), first incisivus right lower (41), and first premolar right lower (44). This study was tested by paired t-test and obtained the value p = 0.000 (p <0.05) so that it can be concluded that gargling with mangosteen fruit peel's extract (Garcinia mangostana Linn) is effective in improving gingival health status on blind in Bhakti Candrasa Sosial Rehabilitation Unit. Keywords: mangosteen fruit peels extract, gingivitis, Modified Gingival Index (MGI), Mastin®, blind.